AHLs Regulate Biofilm Formation and Swimming Motility of Hafnia alvei H4 - Zhu, Yao lei; Hou, Hong man; Zhang, Gong liang; Wang, Yi fang; Hao, Hong shun (Frontiers in Microbiology, 2019)
The aim of this study was to evaluate the role of N-acyl homoserine lactones (AHLs) in the regulation of swimming motility of Hafnia alvei H4 and its biofilm formation on 96-well plate, glass and stainless-steel surfaces. The luxI gene, which codes for an enzyme involved in AHL synthesis, was deleted to generate a luxI mutant (ΔluxI). The mutant produced no AHL, and the relative expression of the luxR gene was significantly (P<0.05) decreased. In addition, qRT-PCR analysis showed that the relative expression of the luxR gene in ΔluxI was stimulated by the presence of exogenous AHLs (C4-HSL, C6-HSL and 3-o-C8-HSL) added at concentrations ranging from of 50-250 µg/ml. Among the three AHLs, C6-HSL had the strongest effect. The ability of ΔluxI to form biofilm on 96-well plate, glass and stainless-steel surfaces was significantly reduced (P<0.05) compared with the wild type (WT), but was increased when provided with 150 µg/ml C4-HSL, whereas C6-HSL and 3-o-C8-HSL had no effect. Scanning electron microscopy (SEM) analysis of the biofilm revealed less bacteria adhering to the surface of stainless-steel and fewer filaments were found binding to the cells compared with the WT. Furthermore, ΔluxI also exhibited significant (P<0.05) decrease in the expression of biofilm- and swimming motility-related genes, flgA, motA and cheA, consistent with the results observed for biofilm formation and swimming motility. Taken together, the results suggested that in H. alvei H4, C4-HSL may act as an important molecular signal through regulating the ability of the cells to form biofilm, as well as through regulating the swimming motility of the cell, and this could provide a new way to control these phenotypes of H. alvei in food processing.